Antarctic chlorine chemistry - Possible global implications - Rodriguez, Jose M.; Ko, Malcolm K. W.; Sze, Nien Dak (1988)
Occurrence of heterogeneous reactions on the surface of polar stratospheric clouds (PSC) is a necessary component of the Cl-related chemical mechanisms proposed to explain the recently observed decrease of O3 during Antarctic spring. A one-dimensional model is used to assess the impact of these heterogeneous reactions on future global O3 trends if they were to occur on the global aerosol layer. The impact of these reactions on the concentration of Cl species in the present-day atmosphere is also calculated. The reaction (ClNO3 + HCl) could have a large impact on stratospheric O3. A fast rate for this reaction would greatly enhance the present concentration of ClO and reduce the abundance of HCl in the lower stratosphere. Because of the large differences between the Antarctic and global environments, the calculated global O3 trends are smaller than those calculated for Antarctica.